2006
DOI: 10.1007/s10658-006-9023-6
|View full text |Cite
|
Sign up to set email alerts
|

Low Input No-till Cereal Production in the Pacific Northwest of the U.S.: The Challenges of Root Diseases

Abstract: Direct-seeding or no-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 49 publications
0
47
0
5
Order By: Relevance
“…For example, in several studies of bare patch (root rot) of wheat, caused by R. solani, reduced tillage led to an increase in severity (24,36,37). It has been suggested that tillage may physically disrupt the fungal hyphae (3,34) or alter the soil microbial community to be suppressive to disease (34). Similarly, root and crown rot in sugar beet, caused by R. solani AG 2-2 IIIB severity, was higher in noncultivated compared with cultivated treatments (5).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in several studies of bare patch (root rot) of wheat, caused by R. solani, reduced tillage led to an increase in severity (24,36,37). It has been suggested that tillage may physically disrupt the fungal hyphae (3,34) or alter the soil microbial community to be suppressive to disease (34). Similarly, root and crown rot in sugar beet, caused by R. solani AG 2-2 IIIB severity, was higher in noncultivated compared with cultivated treatments (5).…”
Section: Discussionmentioning
confidence: 99%
“…Iran is a dry climatic country, and this pathogen occurs under these conditions, being a persistent problem that causes significant losses (Eslahi 2012;Hajieghrari 2009). The symptoms of FRR are often associated with those of FCR because these pathogens are also able to infect the roots and grow to the crown (Paulitz 2006). Disease symptoms include stand reductions, brown discoloration on roots, brown necrotic discoloration of crowns and formation of white heads (Scherm and others 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicates the relative potential of the various R. solani ZG strains, and particularly ZG1-4, ZG1-5, ZG4 and ZG6, to cause serious disease on legume pastures and pose a significant threat to other susceptible rotational crops, especially in no-tillage farming systems (Paulitz 2006). In particular, when choosing pasture legumes as rotation crops, caution needs to be exercised so that the cultivars deployed are those with the best resistance to the R. solani ZGs most likely to be prevalent at the location.…”
Section: Discussionmentioning
confidence: 86%